Case Report: Therapeutic Use of Ibrutinib in a Patient With Schnitzler Syndrome - Huang, Yuehua; Wang, Yanying; Yu, Fan; Mao, Xuehan; Wang, Bianhong; Li, Jingxian; Li, Lihong (Frontiers in Immunology, 2022)
Schnitzler syndrome is a rare adult-onset acquired autoinflammatory disorder typically characterized by chronic urticarial rash and immunoglobulin M (IgM) (rarely IgG) monoclonal gammopathy. Its clinical symptoms usually respond well to interleukin-1 blockade therapy, which, however, does not impact the underlying monoclonal gammopathy. Herein, we described a female patient who presented with urticarial rash, recurrent fevers, and fatigue for 7 years. Laboratory investigations revealed IgMκ monoclonal protein and MYD88 L265P mutation, but no lymphoplasmacytic lymphoma on bone marrow examination. She fulfilled the diagnosis of Schnitzler syndrome and was treated with the Bruton tyrosine kinase inhibitor ibrutinib in combination with prednisone. Her symptoms improved dramatically, and the level of IgMκ monoclonal protein also declined. She tolerated the treatment well. This case highlights the potential therapeutic role of Bruton tyrosine kinase inhibitors in Schnitzler syndrome.